Carbonate Mineral Precipitation for Soil Improvement Through Microbial Denitrification. Issue 2 (7th February 2017) - Hamdan, Nasser; Kavazanjian, Edward; Rittmann, Bruce E.; Karatas, Ismail
ABSTRACT: Microbially induced carbonate precipitation (MICP) and associated biogas production may provide sustainable means of mitigating a number of geotechnical challenges associated with granular soils. MICP can induce interparticle soil cementation, mineral precipitation in soil pore space and/or biogas production to address geotechnical problems such as slope instability, soil erosion and scour, seepage of levees and cutoff walls, low bearing capacity of shallow foundations, and earthquake-induced liquefaction and settlement. Microbial denitrification has potential for improving the mechanical and hydraulic properties of soils because it promotes precipitation of calcium carbonate (CaCO3 ) and produces nitrogen (N2 ) gas without generating toxic by-products. We evaluated the potential for inducing carbonate precipitation in soil via bacterial denitrification using bench-scale experiments with the facultative anaerobe Pseudomonas denitrificans . Bench-scale experiments were conducted (1) without calcium in an N-rich bacterial growth medium in 2.0 L glass batch reactors and (2) with a source of calcium in sand-filled acrylic columns. Changes of pH, alkalinity, NO3 − and NO2 − in the batch reactors and columns, quantification of biogas production and observations of calcium-carbonate precipitation in the sand-filled columns indicate that denitrification led to carbonate precipitation and particle cementation in the pore water as well as a substantial amount of biogas production in both systems. These results document that bacterial denitrification has potential as a soil improvement mechanism.